Mission impossible? Harmonising migration health data across countries. (30th September 2020) - Zenner, D
Abstract: Despite significant efforts, for example within the EU/ EEA, there are currently only few Health information systems (HIS) which are standardized across international borders, and even within countries there can be significant variations. Modalities, technologies and terminologies differ. In the field of migration health, challenges and variations can be more significant. This talk will explore the specific challenges in migration health related HIS, provide an overview of the current HIS landscape pertaining to migration health and sketch out some potential solution to achieve greater harmonization and data sharing across countries.